PERAN PENGURUS PANTI MENUNJANG PENDIDIKAN ANAK DI PANTI ASUHAN GRIYA YATIM DAN DHUAFA BUKITTINGGI - Novika, Rahmi; Arif, M. (El Banar : Jurnal Pendidikan dan Pengajaran, 2024)
The aim of this research is to identify the role of orphanage administrators in supporting children's educational aspirations, the obstacles faced by orphanage administrators in carrying out their duties, and the steps taken by orphanage administrators to overcome these obstacles. Descriptive method was used in this research. Data collection techniques involve direct observation and direct communication, with data collection tools in the form of observation and interviews. The role of orphanage administrators in supporting children's education includes motivator, facilitator, mentor, and substitute parental figure for those who do not have a family. The challenges administrators face often come from the children themselves. The efforts taken by the orphanage management to overcome this obstacle involve a direct approach to the children and providing facilities to meet all the educational needs of the children at the Griya Yatim and Dhuafa Bukittinggi Orphanage